DEVELOPMENT OF SOCIO-CULTURAL COMPETENCE OF STUDENTS BASED ON AUTHENTIC VIDEO: DEVELOPMENT OF SOCIO-CULTURAL COMPETENCE OF STUDENTS BASED ON AUTHENTIC VIDEO - Djumanazarova, M.Djumanazarova (Журнал иностранных языков и лингвистики, 2025)
New paradigms and perspectives in FLT are crucial and essential because of the process of globalization and integration in all spheres of life, new strategies in the social-economic development of Uzbekistan, growth of professional and scientific exchanges, international interaction and cooperation. According to the new paradigms, foreign languages education is the development of a person by means of foreign language at the parallel and interconnected learning of language and culture.